University of Ghana International Travel Policy (May 2011) - Public Affairs (University of Ghana, 2011)
This document outlines the University of Ghana (UG) policy regarding international travel. Staff should consult the UG Local Travel Policy for guidelines on local travel.
University of Ghana Special Reporter
International Travel Policy
Keywords: Report; University of Ghana; International Travel